General Disaster Preparedness Belief Scale Using the Health Belief Model as a Theoretical Framework: Reliability and Validity Measures - Ebru Inal; Kerim Hakan Altintas; Nuri Dogan (International Journal of Assessment Tools in Education)
Disaster preparedness efforts focus predominantly on human behaviors. The Health Belief Model (HBM) is one of the oldest and most widely used modelsin which theory has been adapted from the behavioural sciences to health problems. The study aims to develop and test the psychometric properties of the HBM in relation to General Disaster Preparedness Belief (GDPB). The study was conducted in the city of Yalova among university staff in a Turkish University. A study group of 286 academic and administrative staff completed a HBM scale instrument containing 60 items covering issues related to GDPB. Exploratory Factor Analyses (EFA) was used for the psychometric evaluation and reliability was assessed using item–total correlations and Cronbach’s alpha coefficients using SPSS 19. The EFA extracted six factors that jointly accounted for 59.2% of variance observed namely; Self efficacy (8 items), Cues to action (5 items), perceived susceptibility (6 items), perceived barriers (6 items), perceived benefits (3 items) and perceived severity (3 items). Cronbach’s alpha coefficient for the subscales ranged from 0.90 to 0.74.  The HBM scale for GDPB was found to be a valid and reliable tool. Findings from this study can be used to guide intervention aimed at informing and educating people about disaster preparedness.